2022
DOI: 10.1002/celc.202200188
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Treatment of Persistent Pollutants in Water: General Review of Pharmaceutical Products

Abstract: Environmental problems of great complexity arise from the enormous number of toxic substances that are generated by anthropogenic activities. Seemingly, society encounters new issues every day thus these problems seem to be endless. Now in the face of the COVID‐19 pandemic and the SARS‐CoV‐2 crisis, a large number of emerging treatment compounds generated by pharmaceutical companies worldwide makes future issues even more treacherous. For this reason, there is an increasing need to detect and treat emerging co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 242 publications
0
7
0
Order By: Relevance
“…As a result, pharmaceuticals as an example of these pollutants could be found in receiving surface water. Various studies have confirmed the detection of drugs in the effluent of the conventional methods [92–95] . Bijlsma et al .…”
Section: Water Treatmentmentioning
confidence: 92%
See 1 more Smart Citation
“…As a result, pharmaceuticals as an example of these pollutants could be found in receiving surface water. Various studies have confirmed the detection of drugs in the effluent of the conventional methods [92–95] . Bijlsma et al .…”
Section: Water Treatmentmentioning
confidence: 92%
“…Various studies have confirmed the detection of drugs in the effluent of the conventional methods. [92][93][94][95] Bijlsma et al present a study concerning the occurrence of pharmaceuticals in a conventional WWTP that collects sewage water from an urban region and a near-by hospital. The monitoring data, showed that approximatively 50 % of the pharmaceutical compounds were completely or partially cleared while using conventional biological method.…”
Section: Conventional Waste Water Treatmentmentioning
confidence: 99%
“…[2][3][4] Antibiotics have been used for a long time to prevent bacterial diseases and also to promote the growth of animals around the world. 5 Antibiotics are found in effluents, rivers, and groundwater, 6 due to the irregular disposal of effluents and also the absence of effective remediation methods. 7 The prolonged presence of antibiotics in these media can lead to resistant strains of bacteria, creating an important public health problem.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, many pollutants end up in the environment. [10][11][12] Among the alternative and more environmentally friendly methods, advanced oxidation processes (AOPs) are considered one of the most promising ways to effectively remove several contaminants by oxidizing organic pollutants into harmless compounds. [13][14][15][16][17] These methods allow the in situ generation of hydroxyl radicals that act as non-selective oxidizing agents to destroy non-biodegradable organic molecules in wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…4,6,[18][19][20] These AOPs include catalytic ozonation procedures, sulfate-based AOPs, and treatment with ultrasound, electro-catalytic oxidation, and photocatalysis. 12,[21][22][23][24] Electrocatalytic oxidation has been extensively studied for wastewater treatment due to its simplicity, capacity to mineralize pollutants without producing secondary pollution, and high oxidation rates by losing electrons at the anode or by oxidizing reactive species, leading to the organic pollutant transformation into CO 2 and H 2 O. [25][26][27][28] Direct anodic oxidation occurs at the electrode surface by electron transfer.…”
Section: Introductionmentioning
confidence: 99%